Improvement of methods for determining the cost of design documentation in construction - Dobysheva Tatiana; Gladkova Ekaterina (MATEC Web of Conferences, 2018)
The problems of definition of the cost of design in construction are considered in the article. The existing regulatory documentation for determining the value of construction products on the territory of the Russian Federation is analyzed. A comparative analysis of the currently used methods for calculating the cost of designing is executed. The advantages and disadvantages of each method are considered, and the necessity of transformations in the sphere of determining the cost of design works is substantiated. The ways of increasing accuracy of calculation of the cost of design in construction are suggested, including the use of the territorial coefficient in calculations when utilizing the method of dependence on the natural indicators of the design objects. It is revealed that the use of this coefficient significantly increases the accuracy of calculations. For the method of calculating the cost of design as a percentage of the total cost of construction, it is proposed to clarify the methodology for calculating the cost of construction of multi-apartment buildings according to the enlarged construction price standards. It is proved that today it is impossible to replace the value of individual structural elements of an object in the event of differences in the design solutions with the solutions represented by similar objects in the collection of the construction price standards. The ways of solving these issues by the use of collections of standards for the price of construction solutions are outlined. The authors are convinced that the improvement of methods for calculating the cost of design products will improve the efficiency of investments in the construction industry.